Impacts of Phenolic Compounds and Their Benefits on Human Health: Germination - Jonathan Hernández-Miranda; Karen Argelia Reyes-Portillo; Abigail García-Castro; Esther Ramírez-Moreno; Alma Delia Román-Gutiérrez (Metabolites)
Due to their outstanding nutritional profile, the consumption of seeds has been an essential source of nutrients. These foods have a unique composition, containing carbohydrates, proteins, lipids, fiber, vitamins, minerals, and bioactive compounds in the same food matrix. Furthermore, the nutritional profile can naturally be maximized and optimized through the germination process through two key methods: degradation of macromolecules and biosynthesis of metabolites, which favors an increase in the concentration of bioactive compounds, such as phenolic compounds. The extraction of these compounds has been studied in various plant fractions, including roots, stems, leaves, fruits, and seeds, using different extraction techniques. Among these, ultrasound-assisted extraction has gained popularity due to its efficiency and yield, considering specific parameters to maximize the bioactive yield. These advances have allowed us to evaluate the potential of the extracted compounds as preventive agents in cardiovascular and degenerative diseases, showing promising results in preventive medicine. Recent studies have shown that cereals possess anti-lipid, anti-hypercholesterolemic, anti-diabetic, anti-inflammatory, and antibiotic properties, mainly due to their antioxidant capacity. This work describes the effects of germination on the nutritional profile, presents benefits to human health through seed consumption, and refers to a collection of strategies to improve the extraction process.